2022
DOI: 10.1101/2022.12.13.520227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Striated muscle-specific base editing enables correction of mutations causing dilated cardiomyopathy

Abstract: Dilated cardiomyopathy (DCM) is the second most common cause for heart failure with no cure except a high-risk heart transplantation. Approximately 30% of DCM patients harbor heritable mutations which are amenable to CRISPR-based gene therapy. However, challenges related to delivery of the editing complex and off-target concerns hamper the broad applicability of CRISPR agents in the heart. We employed a combination of the viral gene transfer vector AAVMYO with superior targeting specificity of heart muscle tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…9 We reported similar findings for mice carrying the S637A variant (analogous to S635A in humans). 10 Analysis of other variants in the NLS, including P633L, R634Q, and R636S (number based on the human sequence), in animal models and hiPSC-CMs, 12–18,25,27 have provided further support for the pathogenesis of variants in this portion of the protein.…”
Section: Variants In the Rbm20 Nls Are Causative In Aggressive Dcmmentioning
confidence: 99%
See 4 more Smart Citations
“…9 We reported similar findings for mice carrying the S637A variant (analogous to S635A in humans). 10 Analysis of other variants in the NLS, including P633L, R634Q, and R636S (number based on the human sequence), in animal models and hiPSC-CMs, 12–18,25,27 have provided further support for the pathogenesis of variants in this portion of the protein.…”
Section: Variants In the Rbm20 Nls Are Causative In Aggressive Dcmmentioning
confidence: 99%
“…Recent studies from our laboratory and others have confirmed that NLS-disrupting variants in exon 9 are causative in RBM20 cardiomyopathy using in vivo and in vitro model systems (Table 1). 9,10,12–18,25,27 For example, our laboratory generated mice harboring the S639G variant (analogous to S637G in humans) and showed that these mice develop a severe DCM with early onset heart failure that phenocopies disease in human patients with the same variant. 9 We reported similar findings for mice carrying the S637A variant (analogous to S635A in humans).…”
Section: Variants In the Rbm20 Nls Are Causative In Aggressive Dcmmentioning
confidence: 99%
See 3 more Smart Citations